Metode Yadain Li Tahfizh Al-Qur’an (Implementasi Program Karantina Sebulan Hafal Al-Qur’an di Desa Maniskidul Kuningan Jawa Barat) - Dudung Abdul Karim; Hafid Nur Muhammad; Ali Zaenal Arifin (Studia Quranika, 2020)
Looking after to Qur’an by memorizing it is a requirement for Muslims. however Muslims are still feeling unable to even memorize the Qur’an because several factors,including foreign language and many number of sentences. However, in the “Tahfizh Nasional Quarantine Foundation” has found a mothod that can slowly answer the fear. That is Memorizing Qur’an with “Yadain” Method. Then how to implement of the method. By using field studies, researcher try to explain it in terms of the application and inhibition of these methods. The result of the study revealed that the application of “Yadain” method in the “Tahfizh Nasional Quarantine Foundation” is very easy. It requires us to only focus on the Qur’an and our selves through “taddabur’s” translating. It also implement the application of NLP motivasional training patterns in memorizing of the Qur’an. The inhibitors of this implementation application of methods are considered difficult for those who already has their own methods of memorizing it before following the quarantine. Then, the stages of the application consists of 12 ways that takes a long time for the new participants with the target outcomes of different programs.